2019
DOI: 10.1016/j.dark.2019.100263
|View full text |Cite
|
Sign up to set email alerts
|

Circular motion and energy extraction in a rotating black hole

Abstract: This paper explores the circular geodesics of neutral test particles on an equatorial plane around a rotating black hole. After using equations of motion of scalar-tensor-vector gravity with the circular geodesics of null-like particles, we find the equation of photon orbit. With the help of an effective potential form, we have examined the stable regimes of photons orbits. The Lyapunov exponent, as well as the effective force acting on photons, is also investigated. We examine the energy extraction from a bla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Henceforth, studying a BH's shadow will be a fruitful way for a better understanding of astrophysical BHs, as well as for the comparison of general relativity to those of modern theories [29]. To have information on BHs, the approaches of null geodesics and gravitational lensing are of compelling interest [30,31,32]. Recently, scientists have finally succeeded in obtaining the first-ever image of a supermassive BH, at the centre of the M87 galaxy [33,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Henceforth, studying a BH's shadow will be a fruitful way for a better understanding of astrophysical BHs, as well as for the comparison of general relativity to those of modern theories [29]. To have information on BHs, the approaches of null geodesics and gravitational lensing are of compelling interest [30,31,32]. Recently, scientists have finally succeeded in obtaining the first-ever image of a supermassive BH, at the centre of the M87 galaxy [33,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…For α 2 = 0 and a = 0, the Kerr-MOG BH reduces to the Kerr and Schwarzschild-MOG BH, respectively. For details, see [83,[85][86][87].…”
Section: Kerr-mog Bhsmentioning
confidence: 99%
“…Negative energy states within ergosphere of a BH has essential consequences in BH physics. They could be occurred due to the counter-rotating orbits (as in Kerr BH), as well as due to the electromagnetic interaction (as in RN BH) [37]. Finding the energy limits of a particle is of considerable interest, which they have at a particular position.…”
Section: Negative Energy Statesmentioning
confidence: 99%
“…The evaluation of Penrose mechanism around a non-singular rotating BH, reveals that BH electric charge diminishing the efficiency of energy extraction [36]. While in the case of Kerr-MOG BH, it is the rotational parameter which enriches the efficiency of energy extraction [37]. Recently, Khan et al [38] studied the braneworld Kerr BH and concluded that both spin and brane parameter of the BH, contributes to the efficiency of Penrose mechanism.…”
Section: Introductionmentioning
confidence: 99%